2007
DOI: 10.1891/088667007780477375
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Direct Sensory Exposure to Substantiated Domestic Violence Crimes

Abstract: Police officers served as public health sentinels to collect data on children exposed to domestic violence events (DVEs) across an entire municipality for 1 year. These officers used a standard, validated protocol to collect data on all investigate DVEs. This study extended previous research by including data demographic data on children in the household at the time of the DVE and investigating children's direct sensory exposure to DVEs. Findings revealed that almost half of all events had children present, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…These pathways were partially explained by ASPD, together with additional, smaller effects from psychosis in the case of any adult violence, and alcohol dependence in the case of intimate partner violence. These direct effects of witnessing violence should therefore be considered in the context of previous studies showing that childhood abusive experiences and IPV (witnessed by the child) co-occur and increase risk for each other (Appel & Holden, 1998;Fantuzzo & Fusco, 2007;McCloskey, Figueredo, & Koss, 1995;Moffitt & Caspi, 2003). Furthermore, that additional factors commonly present among family members include substance misuse, criminality, psychiatric morbidity, neighborhood disadvantage, and violence toward others outside of the home (Herrenkohl, Sousa, Tajima, Herrenkohl, & Moylan, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…These pathways were partially explained by ASPD, together with additional, smaller effects from psychosis in the case of any adult violence, and alcohol dependence in the case of intimate partner violence. These direct effects of witnessing violence should therefore be considered in the context of previous studies showing that childhood abusive experiences and IPV (witnessed by the child) co-occur and increase risk for each other (Appel & Holden, 1998;Fantuzzo & Fusco, 2007;McCloskey, Figueredo, & Koss, 1995;Moffitt & Caspi, 2003). Furthermore, that additional factors commonly present among family members include substance misuse, criminality, psychiatric morbidity, neighborhood disadvantage, and violence toward others outside of the home (Herrenkohl, Sousa, Tajima, Herrenkohl, & Moylan, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…If so, this is particularly important because exposure to traumatic events during early childhood has been associated with more negative outcomes than later exposure. Research suggests that young children are more negatively affected by trauma exposure because, in early childhood, the developing brain is vulnerable, attachment formation occurs, and developmental tasks are paramount (Fantuzzo & Fusco, 2007;Manly, Kim, Rogosch & Cicchetti, 2001;Swick, Knopf, Williams & Fields, 2013). For early childhood SOCs, other trauma-informed models or training approaches that have demonstrated promising findings in Head Start or other early intervention sites could be adapted.…”
Section: Discussionmentioning
confidence: 99%
“…Residing in a household with IPV puts children at risk for being exposed to and witnessing violence (Graham-Bermann et al 2007). Fantuzzo and Fusco (2007) reported that children under the age of 6 years old are disproportionately exposed to IPV events and are at a greater risk of direct exposure to these events as compared to older, school-aged children. They noted that of the children who were present during events involving IPV, 81 % had direct exposure to these violent incidents (Fantuzzo and Fusco 2007).…”
Section: Ipv In the Lives Of Young Childrenmentioning
confidence: 99%
“…Fantuzzo and Fusco (2007) reported that children under the age of 6 years old are disproportionately exposed to IPV events and are at a greater risk of direct exposure to these events as compared to older, school-aged children. They noted that of the children who were present during events involving IPV, 81 % had direct exposure to these violent incidents (Fantuzzo and Fusco 2007). Graham-Bermann and colleagues (2007) further assessed whether children were direct witnesses to mothers' reports of IPV events and found 89 % were eyewitness to psychological maltreatment and 82 % witnessed physical violence in the home when it occurred.…”
Section: Ipv In the Lives Of Young Childrenmentioning
confidence: 99%